DEVELOPMENT OF AN AUGMENTED REALITY-BASED MAGAZINE TO REDUCE MISCONCEPTIONS ABOUT THREE-DIMENSIONAL SHAPES AMONG ELEMENTARY SCHOOL STUDENTS - Dedy Susetyo Aji; Subuh Anggoro (SOSIOEDUKASI, 2026)
Mathematics plays an important role in developing logical thinking skills, yet learning media remain limited. This study aims to develop an Augmented Reality (AR)-based learning media entitled “Jelajah Dunia Bangun Ruang”, specifically designed to reduce misconceptions about three-dimensional shapes in elementary school. This research uses a Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The sample consisted of 41 fifth-grade students from the Ki Hajar Dewantara Cluster in Banjarnegara (21 students in the control group and 21 students in the experimental group). Data were collected through expert validation questionnaires, misconception diagnostic tests based on the Certainty of Response Index (CRI), and documentation. Data analysis was conducted using SPSS, including validity, reliability, normality, homogeneity, and hypothesis testing. The results show that the AR-based magazine is highly feasible for use in learning (media experts 100%, content experts 95.38%, language experts 95.56%). The experimental group achieved higher learning outcomes (13.86) compared to the control group (11.90). In addition, the Mann–Whitney test (p = 0.000 < 0.05) indicates a significant difference between the two groups. Thus, AR-based media is proven to be more effective in improving conceptual understanding and reducing misconceptions about three-dimensional shapes in elementary school. Teachers are recommended to gradually integrate Augmented Reality media to enhance understanding and reduce misconceptions.